Outcomes Following Gender Affirming Phalloplasty: A Systematic Review and Meta-Analysis. (26th August 2022) - Wang, Annie M.Q.; Tsang, Vivian; Mankowski, Peter; Demsey, Daniel; Kavanagh, Alex; Genoway, Krista
Abstract: Introduction: Phalloplasty is one of the genital genders affirming surgeries sought by transmasculine transgender patients during transition. Despite current advances in surgical techniques, the lack of consistency in outcomes evaluation for phalloplasty leads to significant challenges in guiding patients in clinical decision making. Aims: This systematic review and meta-analysis aims to assess outcomes for different phalloplasty surgical techniques. Methods: The literature was searched using Medical Literature Analysis and Retrieval System Online (MEDLINE; PubMed), Excerpta Medica database, and Cochrane Database of Systematic Reviews. All English-language randomized control trials, prospective and retrospective cohort studies, case series, and case reports of at least 4 patients were included. The primary outcome was postoperative complications, and the secondary outcomes were functional and aesthetic results. Proportional meta-analysis was used to pool complication rates using a random-effects model. Results: Database searching generated 39 final articles, with 19 case series, 3 cross-sectional studies, and 17 retrospective cohort studies. A total of 1731 patients underwent phalloplasty, with the most common type of reconstruction performed being the radial forearm free flap (75.1%). Overall complication rate was high at 76.5%, of which urethral complications were high in all reconstructive subgroups (urethral fistula rate of 34.1% and urethral stricture rate of 25.4%). Postoperative functional outcomes were reported in 57.6% of patients, finding that most had tactile sensation (93.9%) and can void while standing (92.2%). Aesthetic outcomes were only reported in 6.3% of patients, with mean length achieved being 12.26 cm (SD = 0.81 cm) and mean circumference being 10.18 cm (SD = 3.69 cm). Conclusion: In the transmasculine transgender population, current evidence of the various phalloplasty surgical techniques and their expected postoperative outcomes is weak. Future research may consider developing a standardized core outcome set to improve clinical decision making.